2019
DOI: 10.1029/2018jd029409
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Weather Patterns Modulate Air Quality in Eastern China During 2015–2016 Winter

Abstract: The roles of anthropogenic emissions and weather conditions in air pollution over eastern China have been widely discussed but still controversial. Here we focus on the impact of the intraseasonal variability of midtropospheric weather circulations on air quality during 2015–2016 winter. We use the European Center for Medium‐Range Weather Forecasts reanalysis data to calculate westerly wind index (WI) and meridionality in the midtroposphere and also calculate the intensity of Siberian High at the surface. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Considering that meteorological events generally have a strong influence on the concentrations of pollutants in the air ( Baklanov et al, 2016 ; Borge et al, 2019 ; Zhao et al, 2019 ), the meteorological data collected in cities have been studied ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that meteorological events generally have a strong influence on the concentrations of pollutants in the air ( Baklanov et al, 2016 ; Borge et al, 2019 ; Zhao et al, 2019 ), the meteorological data collected in cities have been studied ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The meteorological data were sorted in climatically homogeneous reference periods for the comparison of the different scenarios, namely, no limitations, considered PL and TL. This aspect is essential considering that weather phenomena have a massive influence on air quality (Baklanov et al, 2016;Borge et al, 2019;Demuzere et al, 2009;Jhun et al, 2015;Zhao et al, 2019). January was not considered suitable for the identification of the reference period due to the high relative humidity, and low average temperatures (Table S3), different conditions than PL and TL which would have led to an imbalance in the comparison of some polluting agent trends (e.g.…”
Section: Meteorological Data Analysis For Reference Period Selectionmentioning
confidence: 99%
“…More specifically, the strength of the Siberian High was defined as the mean sea level pressure over Mongolia and southern Siberia between 80-120 °E and 40-65 °N (black box in Figure 2) [32]. Previous studies have shown that this definition successfully represented the strength of the Siberian High using not only climate studies but also air quality studies [33,34]. Surface temperature, sea level pressure, surface wind, and relative humidity data were obtained from the Seoul station of the Korea Meteorological Administration [28] for the same period (red dot in Figure 1).…”
Section: Domain and Datamentioning
confidence: 99%
“…More specifically, the strength of the Siberian High was defined as the mean sea level pressure over Mongolia and southern Siberia between 80-120 • E and 40-65 • N (black box in Figure 2) [32]. Previous studies have shown that this definition successfully represented the strength of the Siberian High using not only climate studies but also air quality studies [33,34]. The Siberian High has the most significant influence on winter climate over the Eurasian continent, including East Asia [30,31], as the position and strength of the Siberian High controls the synoptic systems over this area.…”
Section: Domain and Datamentioning
confidence: 99%